Expressão e localização de aquaporinas no epidídimo do gerbilo, Meriones unguiculatus, em diferentes fases do desenvolvimento pós-natal - Machado, Carla de Moraes [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Aquaporins (AQPs) are membrane protein channels expressed in a wide variety of cells and tissues that are involved in the transport of water. In the male excurrent duct, the movement of fluid and solutes across the epithelium is essential for establishing the proper luminal environment in which sperm mature and are stored. The initial aim of the present propose is to localize AQP 2 e 9 in epithelium of the initial segment, caput, corpus and cauda epididymidis in Mongolian gerbil during postnatal development (10, 30, 60, 120 and 300 days), observing possible changes in the pattern of expression of the AQPs along the postnatal development. The animals will be killed by inhalation of carbon dioxide. After euthanasia, the epididymis will be removed and the different regions will be isolated. The biological material obtained will be processed in accordance with the routines of histological techniques and imunnohistochemistry to study the expression and localization of the AQPs 2 and 9. The results obtained will be analyzed and photographed in conventional light microscope

As aquaporinas (AQPs) são proteínas expressadas na membrana plasmática de diferentes tipos celulares e tecidos envolvidos no transporte de fluidos. No sistema genital masculino, o movimento de fluidos e solutos através do epitélio é essencial para a formação e manutenção do fluido luminal. Esta proposta tem como objetivo estudar a localização das AQPs 2 e 9 no epitélio de revestimento do segmento inicial, cabeça, corpo e cauda do epidídimo de gerbilos em diferentes faixas etárias (10, 30, 60, 120 e 300 dias de idade), observando possíveis alterações no padrão de expressão das AQPs ao longo do desenvolvimento pós-natal. Para realização deste projeto, os animais foram submetidos à eutanásia em câmara de CO2, e após a coleta dos epidídimos, as diferentes regiões foram isoladas. O material biológico obtido foi processado segundo as rotinas histológica e imunoistoquímica para estudo da expressão e localização das AQPs 2 e 9. Os resultados obtidos foram analisados e fotodocumentados em microscópio de luz convencional
Keywords: Celulas epiteliais; Epitelio; Epidídimo; Rato - Estudos experimentais; Epithelium